Joint linear transceiver design over MIMO frequency selective channels - HAN Sheng-qian; YANG Chen-yang (Tongxin xuebao)
The problem of joint linear spatial Tx-Rx design was investigated for multiple-antenna non-block transmission systems over frequency selective channels. A minimum mean square error （MMSE） criterion based linear transceiver was proposed. To avoid the iterative computation between the transmitter and receiver involved in the joint MMSE Tx-Rx design, a low-complexity transceiver given a MMSE receiver called successive searching zero-forcing （ZF-SS） algorithm was proposed, which exploits spatial resources to mitigate or eliminate the inter-symbol-interference caused by multi-path channels. Simulation results show that both the MMSE algorithm and the ZF-SS algorithm outperform the existing eigenvalue based beamformer for high signal-to-noise ratio （SNR）.